2016
DOI: 10.18203/2349-2902.isj20160237
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of intrathecal bupivacaine 0.5% with bupivacaine 0.5% and buprenorphine low dose for postoperative analgesia in lower abdominal surgeries

Abstract: INTRODUCTIONPain is one of the most common and uncomfortable consequences of a surgery, feared by all. Effective and rapid relief from pain is always a challenge, but is necessary for alleviating nocioception -induced responses like endocrine metabolic responses to surgery, autonomic reflexes with adverse effects on organ function, reflexes leading to muscle spasm, and other undesirable results. 1 ABSTRACT Background: Opiods, like buprenorphine, have been widely used for providing pain relief postoperatively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…[ 12 14 16 ] Lower or no bradycardia with lower doses of buprenorphine in our study was supported by studies elsewhere. [ 13 15 17 18 19 ] Our observation of a higher incidence of hypotension in higher doses of buprenorphine (150 μg) compared to lower doses was similar to a study by Mishra and Maharana who reported a significant change in mean arterial pressure with higher doses of buprenorphine. [ 16 ] Other studies also supported our findings on incidences of hypotension with different doses of buprenorphine.…”
Section: Discussionsupporting
confidence: 84%
“…[ 12 14 16 ] Lower or no bradycardia with lower doses of buprenorphine in our study was supported by studies elsewhere. [ 13 15 17 18 19 ] Our observation of a higher incidence of hypotension in higher doses of buprenorphine (150 μg) compared to lower doses was similar to a study by Mishra and Maharana who reported a significant change in mean arterial pressure with higher doses of buprenorphine. [ 16 ] Other studies also supported our findings on incidences of hypotension with different doses of buprenorphine.…”
Section: Discussionsupporting
confidence: 84%